Assessing Greece’s social vulnerability patterns in times of perma-crisis (2008–2022) - Melidis, Michail; Tzagkarakis, Stylianos Ioannis; Papadakis, Nikos (Frontiers in Political Science, 2024)
IntroductionThe study aims to map and analyse the development of social vulnerability patterns in Greece through a perma-crisis context (economic crisis, austerity, covid-19, energy, and inflation crisis) over the period 2008-2022.MethodsThe paper rests on the construction of a composite index of four key pillars of social vulnerability (employment, living conditions, health, and education) consisting of 15 selected variables obtained from the official Eurostat datasets and using PCA analysis.ResultsOur findings show that social vulnerability patterns in Greece demonstrate a considerable shift during the stated period where certain social groups (i.e., NEETs and precarious workers) seem to suffer the most. The first pattern (2008-2016) is largely characterized by the intensity and severity of the economic crisis and austerity measures, which contributed to the exacerbation of social vulnerability. The second pattern (2017-2022) presents a gradual decline mainly due to the recovery of the economy and a decrease in unemployment rates featuring a strong tendency to reach the pre-crisis levels in the years to come.DiscussionThe high levels of social vulnerability leading to social exclusion, poverty, and the widening of inequalities, impede the country’s resilience and recovery efforts and undermine social cohesion.